Proteomic analysis of egg production peak and senescence in the ovaries of Taihe black-boned silky fowl (Gallus gallus domesticus Brisson) - Xuan Huang; Shibao Li; Yuting Tan; Chunhui Xu; Yunyan Huang; Zhaozheng Yin (BMC Genomics)
Abstract Background The Taihe black-boned silky fowl, a distinguished indigenous breed of chicken, is renowned for its dual utility in both traditional medicinal and culinary applications. However, the breed faces significant challenges due to its suboptimal reproductive capabilities and a notably brief egg-laying period, which have impeded its broader development and cultivation. In this research endeavor, we employed an advanced, rapid DIA (Data independent acquisition) quantitative proteomics method on the Astral platform to meticulously analyze the ovarian proteome of these chickens. By analyzing the ovarian proteomic information of Taihe black-boned silky fowl during peak and decline egg-laying periods, we aim to identify potential reproductive candidate proteins and the molecular mechanisms underlying egg-laying decline. This could enable us to implement interventions to improve the reproductive efficiency of this valuable breed. Result In this study, a total of 8,281 proteins were identified within the ovarian proteome of the Taihe black-boned silky fowl. Among these, 303 proteins exhibited significant differential expression, with 98 proteins significantly up-regulated and 205 proteins significantly down-regulated. The functional annotation of these proteins illuminated their crucial roles in the steroid hormone synthesis pathways, which are pivotal during the peak of egg production. Furthermore, during the later stages of laying, there was a noticeable upregulation of proteins associated with inflammatory senescence and oxidative stress. This change suggests an increase in reproductive stress within the ovary, highlighting the physiological shifts that affect productivity as the chickens age. Conclusion This study identified key candidate protein markers in the Taihe black-boned silky fowl during critical phases of their reproductive cycle, specifically peak and late egg-laying periods. These findings contribute valuable new scientific insights that can be utilized for the breeding optimization and effective management of this unique breed. By elucidating the protein dynamics during different laying phases, the research offers potential strategies aimed at enhancing reproductive performance and extending the reproductive lifespan of the Taihe black-boned silky fowl. This could lead to significant improvements in both the sustainability and profitability of farming this indigenous breed.